Legitmasi Nasab dan Strategi Dakwah Habib Ba’alwi dalam Perspektif Muhammadiyah - Hasanudin; Setiarso, Gunawan (Penerbit Minhaj Pustaka, 2025)
Habib is widely known by the Indonesian Muslim community as a descendant of the Prophet Muhammad SAW. The habaib in Indonesia are descendants of Alwi or better known as Bani Alwi or Ba'alwi who migrated to Indonesia with immigrants from Arab Hadramaut Yemen in the 19th-20th centuries AD. The understanding of habib as a descendant of the Prophet Muhammad SAW, makes the Indonesian Muslim community very respectful, and follows what is ordered because they are afraid of curses and not getting the intercession of the Prophet Muhammad SAW in the afterlife. This understanding is gradually being deconstructed with the research of K.H. Imaduddin Utsman Al Bantani